Baremos físicos para detección y selección general de talentos deportivos del Cantón Rumiñahui - Paucar Tipán, M. G.; Calero Morales, S. (Lecturas: Educación Física y Deportes, 2018)
There is no scale in Ruminahui Canton for sports trainers to reference the standards on detection and selection of new talents no matter the sport they practice, so as a consequence of the lack of a scientific basement, the process is not as effective as it should be. The goal is to stablish general detection scales for sports talents in Ruminahui Canton through the application of scientific methods such as anthropometric measures and most of all, physical tests to facilitate the effective formation of new sports talents in sports schools in Canton. The candidates (children/teenagers) were tested in similar conditions by applying anthropometric measures and physical tests. The sample is composed by 323 children/teenagers both, male and female, between 9-12 years old. The following anthropometric measures and physical tests were applied: weight (kg), height (cm), flexibility: vertical anterior trunk flexion (cm), jump length s/c impulse (cm), back throw with medicine ball 2 kg s/c of impulse (cm), 30 m speed (sec.), abdominal 30 secs. (Rep.) stroke of 600 m up to 10 years and for 11-12 years a distance of 1000 m (in sec), push-ups and extensions of elbow mouth down 30 sec. (Rep.). The established scales at an anthropometric and physical level, are indicators to set a more adequate and precise orientation up, helping trainers to go through a more accurate process regarding the detection and selection in sports schools in Ruminahui Canton.